2021
DOI: 10.1038/s41598-021-87171-5
|View full text |Cite
|
Sign up to set email alerts
|

Development of machine learning model for diagnostic disease prediction based on laboratory tests

Abstract: The use of deep learning and machine learning (ML) in medical science is increasing, particularly in the visual, audio, and language data fields. We aimed to build a new optimized ensemble model by blending a DNN (deep neural network) model with two ML models for disease prediction using laboratory test results. 86 attributes (laboratory tests) were selected from datasets based on value counts, clinical importance-related features, and missing values. We collected sample datasets on 5145 cases, including 326,6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(51 citation statements)
references
References 41 publications
1
50
0
Order By: Relevance
“…Three common indicators-Sensitivity, Specificity, and Precision-are defined below Accuracy [34] is defined as: F1 score considers both the precision and the sensitivity [35]. It is the harmonic mean of the previous two measures: precision and sensitivity.…”
Section: Measures and Indicatorsmentioning
confidence: 99%
“…Three common indicators-Sensitivity, Specificity, and Precision-are defined below Accuracy [34] is defined as: F1 score considers both the precision and the sensitivity [35]. It is the harmonic mean of the previous two measures: precision and sensitivity.…”
Section: Measures and Indicatorsmentioning
confidence: 99%
“…In this study, the author assessed the predictability of commonly used supervised algorithms to detect blood diseases, and they achieved ~98% accuracy to predict the occurrence of blood disease with LogitBoost algorithms [ 108 ]. Park et al built three models, LightGBM and extreme gradient boosting (XGBoost) ML models and a DNN (deep neural network) based model on 5145 cases and 326686 laboratory tests [ 109 ]. The authors proposed that among the three models, the ensemble model showed 81% F1-score and ~92% prediction accuracy against the most common diseases [ 109 ].…”
Section: Role Of Ai In the Screening Of Covid-19 Infected Patients And Diagnosismentioning
confidence: 99%
“…Park et al built three models, LightGBM and extreme gradient boosting (XGBoost) ML models and a DNN (deep neural network) based model on 5145 cases and 326686 laboratory tests [ 109 ]. The authors proposed that among the three models, the ensemble model showed 81% F1-score and ~92% prediction accuracy against the most common diseases [ 109 ]. Not only does this blood analysis detect the disease, but it can also tell about the severity of a disease.…”
Section: Role Of Ai In the Screening Of Covid-19 Infected Patients And Diagnosismentioning
confidence: 99%
“…And, for performance enhancement, ensemble machine learning and deep learning model can be used [21,22]. In the healthcare domain, artificial intelligence (AI) plays a major role in automating the roles involved in disease diagnosis and treatment suggestions and also schedules perfect timing by the medical practitioners to perform various obligations that cannot be automated [23].…”
Section: Introductionmentioning
confidence: 99%